Erythropoietin and Hypericum perforatum ameliorate Gentamicin-induced nephrotoxicity in rats - Ak, Tuba Parlak; Sagiroglu, Meltem; Korkmaz, Gizem Elif; Yaman, Mine (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
Gentamicin (GM), which causes nephrotoxicity, is an aminoglycoside antibiotic commonly prescribed to treat of gram-negative infections. Erythropoietin (EPO), which has several biological functions including neuroprotection, wound healing and nephroprotection, is a glycoprotein hormone that controls erythropoiesis. Hypericum perforatum (HP) is a medicinal herb with antibacterial and nephroprotective effects. The aim of this study is to demonstrate the efficacy of EPO and HP in GM nephrotoxicity using combined biochemical, histopathological and immunohistochemical evaluations together. A total of 36 male Spraque-Dawley rats were divided into as control, GM (100 mgkg-1-1 day), GM+EPO, GM+HP, EPO (1000 IUkg-1three-1 three consecutive days apart) and HP (200 mgkg-1-1 day) groups (n=6) and the experiment lasted for 9 days. GM-induced increased relative kidney weight and increased serum urea nitrogen (BUN), creatinine and urea levels were reduced by EPO and HP. EPO and HP reduced the level of malondialdehyde (MDA), which increased with GM application, and increased the activities of reduced glutathione (GSH), glutathione peroxidase (GSH-Px), and catalase (CAT). GM nephrotoxicity resulted in tubular degeneration, vacuolization and hyaline deposits, glomerular degeneration and interstitial mononuclear cell infiltration. EPO and HP attenuated these histopathological changes. Also, EPO and HP also reduced caspase-3 immunoreactivities, which increased with GM application. It was shown that EPO and HP have attenuating effects on GM-induced kidney injury, and especially the intense antioxidant content of HP has a regulatory effect on the negative consequences of oxidative stress.
La eritropoyetina y el Hypericum perforatum mejoran la nefrotoxicidad inducida por gentamicina en ratas
Keywords: Apoptosis; Erythropoietin; gentamicin; Hypericum; perforatum; oxidative stress